Dakwah Kultural KH. Imam Nawawi di Magetan - Mukhlis, Zainal (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2020)
This articel attempts to examine the role of KH Imam Nawawi in conducting a cultural da'wah within local community in Parang District, Magetan Regency, East Java. The research method used in this study is a descriptive qualitative and historical approach. The findings illustrate that cutural Islamic propagation conducted KH Imam Nawawi is able to change Javanese culture to local Islamic traditions in Parang district. Further, he has changed people’s religious faith and behavior to become more in line with Islamic teachings. Additionally, kiai Imam Nawawi has emphasized his da’wah activities not to eliminate Javanese local culture since he regards that local tradition resulted from local community creation that should be preserved.